Pengaruh Legalitas Usaha dan Kualitas Produk terhadap Keputusan Pembelian Konsumen pada UMKM Binaan Dinas Koperasi dan UKM Provinsi - Azzahra Ramadani Marsanda; Novita Ekasari; Yayuk Sriayudha (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the effect of business legality and product quality on consumer purchase decisions at SMEs fostered by the Jambi Province Office of Cooperatives and SMEs. This study employed a quantitative approach with a sample of 96 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that business legality has a positive and significant effect on consumer purchase decisions, with a significance value of 0.043 (< 0.05). Product quality also has a positive and significant effect on purchase decisions, with a significance value of < 0.001. Simultaneously, business legality and product quality have a positive and significant effect on consumer purchase decisions, with a significance value of < 0.001. The coefficient of determination (R²) of 0.477 indicates that both variables explain 47.7% of the variation in consumer purchase decisions. Therefore, business legality and product quality are important factors influencing consumer purchase decisions at SMEs fostered by the Jambi Province Office of Cooperatives and SMEs.